Assessment of the calendar aging of lithium-ion batteries for a long-term—Space missions - Ali, Hayder; Beltran, Hector; Lindsey, Nancy J.; Pecht, Michael (Frontiers in Energy Research, 2023)
Energy availability is a critical challenge for space missions, especially for those missions designed to last many decades. Space satellites have depended on various combinations of radioisotope thermoelectric generators (RGTs), solar arrays, and batteries for power. For deep space missions lasting as long as 50+ years, batteries will also be needed for applications when there is no sunlight and RTGs cannot support peak power demand due to their insufficient specific power. This paper addresses the potential use of lithium-ion batteries for long-term space missions. Using data collected from the literature and internal experiments, a calendar aging model is developed to assess the capacity fade as a function of temperature, state-of-charge and time. The results for various LIB chemistries are used to identify the best candidate chemistries and determine the conditions, with a focus on low temperatures, that can best enable deep space missions.